Formation of silver wires embedded in hydrogels using femtosecond laser ablation and electroplating for strain sensing. (1st December 2022) - Zhao, Pingping; Hu, Jian; Chen, Tao; Si, Jinhai; Wu, Jingping; Zhang, Yu; Li, Kaidi; Hou, Xun
Abstract: The formation process of conductive silver wires embedded in hydrogels using femtosecond laser ablation and electroplating was investigated. Implanted needle electrode was used as the cathode instead of a plate cathode in the previous report to perform electroplating. This improvement made reduced silver microstructures much easier to grow into the femtosecond-laser-ablated microchannels in the hydrogels, forming silver wires up to 20 mm long, one order of magnitude larger than the reported results. It also makes the growth process of the reduced microstructures observable. Results show that the growth speed increased with the increase of current and the decrease of femtosecond laser power and scanning speed. Besides, smooth and dense silver wires were formed at the optimal condition of a current of 5 mA, femtosecond laser power of 3 mW, and scanning speed of 10 μ m s −1 . Its resistivity was as low as ∼2.84 × 10 −7 Ω m, smaller than that of rough silver wires. Moreover, the strain sensing performance of the formed silver wires embedded in the hydrogel was studied, which showed good repeatability (7% to 13% strain) and high sensitivity (gauge factor up to 14). It may open up a facile scalable technique for the design and fabrication of the metal-patterned component embedded in hydrogel for flexible and wearable electronics.